2019
DOI: 10.1021/acs.jproteome.9b00701
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Comparison of Label-Free, SILAC, and TMT Techniques to Study Early Adaption toward Inhibition of EGFR Signaling in the Colorectal Cancer Cell Line DiFi

Abstract: We evaluated the quantification strategies label-free (LF), stable isotope labeling by amino acids in cell culture (SILAC), and tandem mass tags (TMT) and their performance in quantification of proteins and phosphosites (p-sites) to identify the most powerful approach for monitoring cellular signaling. We analyzed the epidermal growth factor receptor (EGFR) signaling network, which plays an essential role in colorectal cancer, and studied its dynamics within 24 h upon treatment with the EGFR-blocking antibody … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 55 publications
(89 reference statements)
2
40
0
Order By: Relevance
“…Nevertheless, the precision advantage of label‐based approaches could be less impactful on larger sample sets. In fact, some authors have reported a decrease in performance when multiple isobaric labelling experiments are combined into a single data analysis pipeline, with increasing missing values and decreased precision 27,30 . The same drawback could be even more relevant for MS 1 ‐based quantification methods (SILAC/DML) because of their limited multiplexing capabilities.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, the precision advantage of label‐based approaches could be less impactful on larger sample sets. In fact, some authors have reported a decrease in performance when multiple isobaric labelling experiments are combined into a single data analysis pipeline, with increasing missing values and decreased precision 27,30 . The same drawback could be even more relevant for MS 1 ‐based quantification methods (SILAC/DML) because of their limited multiplexing capabilities.…”
Section: Resultsmentioning
confidence: 99%
“…increasing missing values and decreased precision. 27,30 The same drawback could be even more relevant for MS 1 Marco Gaspari https://orcid.org/0000-0002-5411-8800…”
Section: Final Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Publicly available proteomic data were used for the AA_stat evaluation. [25][26][27][28][29][30][31][32] Detailed annotation of these datasets is provided in Supporting Information (S-Table 1). Their selection was aimed at having a diverse number of modified amino acid residues per peptide.…”
Section: Methodsmentioning
confidence: 99%
“…Table 4 summarizes the sets of fixed and variable modifications recommended by AA_stat in comparison with the modification sets from annotation of the respective studies. [24][25][26][27][28][29][30][31] Comparing the annotated and AA_stat-retrieved modifications, both expected and unexpected modifications can be mentioned. For example, Cys-carbamidomethylation was annotated for all data, however, two subsets with enrichments of phosphorylated peptides (#9, #10 in Figure 2) and one subset with R-methylation enrichment (#12 in AA_stat demonstrates a potential for uncovering rare modifications.…”
Section: Overviewmentioning
confidence: 95%